Shaping the Brand Awareness of Science and Technology Parks in Eastern Poland - Anna Lis; Ewa Romanowska (Barometr Regionalny, 2016)
The main aim of the paper is the analysis of the effects of actions undertaken so far that have aimed at shaping brand awareness of the parks in Eastern Poland supported under the Operational Programme Development of Eastern Poland. The authors focused on the demand-side perspective and scrutinized two vectors of conscious branding: the surrounding environment and communication with customers. The group of potential customers underwent qualitative research (ITI interviews). The research in the group of the actual customers was conducted by means of quantitative methods (CAPI and CATI interviews). The results of the study indicate the lack of knowledge of the parks’ functioning, the lack of awareness of the benefits that could be achieved while cooperating with parks, low effectiveness of the existing forms of promotion of the parks, but also the high needs for innovation support among entrepreneurs. On the basis of the study results, the authors formulated recommendations for improving the promotion of parks.